Establishing geochemical baselines in forest soils for environmental risk assessment in the Montague and Goldenville gold districts, Nova Scotia, Canada - Parsons, Michael B.; Little, Megan E. (Atlantic Geoscience, 2015)
Mine tailings at historical gold districts in Nova Scotia, Canada, contain high concentrations of arsenic (As) and mercury (Hg), which may represent a risk to ecosystems and human health. Two sites, Montague and Goldenville, are of particular concern as tailings are located close to residences and are occasionally used for racing off-road vehicles. Risk-assessment calculations require knowledge of the naturally occurring concentrations of As and Hg in soils overlying mineralized bedrock within these gold districts. In this study, we collected samples of the top 0–5 cm of surface soil (the Public Health layer) from 46 sites near Montague, and 39 sites near Goldenville. Samples of individual soil horizons (H, Ae, B, and C) were also taken from selected sites to evaluate the vertical distribution of elements in the soil profile. Results show that the concentrations of As and Hg in all soil horizons are generally higher down-ice, southeasterly, of the ore zones in both districts, reflecting glacial erosion and transport of mineralized bedrock. Analysis of the top 0–5 cm of soils shows the following ranges in As and Hg concentrations (<2 mm size fraction): Montague: As, 4–273 mg/kg (median 42 mg/kg); Hg, 72–490 µg/kg (median 164 µg/kg); Goldenville: As, 2–140 mg/kg (median 13 mg/kg); Hg, 39–312 µg/kg (median 114 µg/kg). In general, the concentrations of As are highest in the B and C horizons, whereas Hg concentrations are highest in humus (H). Results from this study have been used to assess the distribution of tailings at these sites, and to help guide risk-management decisions.